Copper‐Based Corrole as Thermally Stable Hole Transporting Material for Perovskite Photovoltaics. (9th September 2020) - Agresti, Antonio; Berionni Berna, Beatrice; Pescetelli, Sara; Catini, Alexandro; Menchini, Francesca; Di Natale, Corrrado; Paolesse, Roberto; Di Carlo, Aldo
Abstract: Perovskite solar cells (PSCs) represent nowadays a promising starting point to develop a new efficient and low‐cost photovoltaic technology due to the demonstrated power conversion efficiency (PCE) exceeding 25% on small area devices. However, best reported devices suffer from stability issue under real working conditions thus slowing down the race for the commercialization. In particular, the hole transporting material commonly employed in mesoscopic n–i–p PSCs (nip‐mPSCs), namely spiro‐OMeTAD, is strongly corrupted when subjected to temperatures above 70 °C due to intrinsic thermal instability and because of the dopant employed to improve the hole mobility. In this work, the novel use of a copper‐based corrole as HTM is proposed to improve the device thermal stability of nip‐mPSCs under prolonged 85 °C stress conditions. Corrole‐based devices show remarkable PCE above 16% by retaining more than 65% of the initial PCE after 1000 h of thermal stress, while spiro‐OMeTAD cells abruptly lose more than 60% after the first 40 h. Once scaled‐up to large area modules, the proposed device structure can truly represent a possible way to pass thermal stress tests proposed by IEC‐61646 standards and, not less importantly, the high temperature required by the lamination process for panel production. Abstract : The novel use of cheap copper‐based corrole as hole transporting material in perovskite solar cells is shown by improving the device thermal stability of n–i–p mesoscopic architecture under prolonged 85 °C stress conditions. Corrole‐based devices show a remarkable power conversion efficiency above 16% by retaining more than 65% of the initial power conversion efficiency after 1000 h of thermal stress.